PELATIHAN PRAKTIK ILMU YANG BERKAITAN DENGAN PELEDAKAN BATUAN DAN PENGANTAR ILMU KETEKNIKAN KEPADA SISWA SMKN 4 PALANGKARAYA - Jarwanto, Jarwanto (Nusantara Hasana Journal, 2025)
This Community Service activity is entitled "practical training related to rock blasting and an introduction to engineering science for students at SMKN 4 Palangkaraya." The objectives of this activity are to strengthen the relationship between the school and the community, apply students' knowledge and skills, develop soft skills, increase social and environmental awareness, and introduce the world of mining in a positive way. The activity method used is lectures or counseling and practical exercises at SMKN 4 Palangkaraya. The results of this activity are: Implementation of the Community Service Program (PKM) is carried out by providing students with mastery of understanding and skills in dealing with learning methods and mastering the material. Direct understanding is achieved through practical methods in the field regarding the blasting process, which is preceded by an opening and introductory activity on the rock blasting process. Following the field activity, a Zoom meeting was conducted directly from the AKPRIND Indonesia University campus by lecturers in the Geological Engineering Study Program, presenting material on rocks, minerals, engineering, and petroleum.